Bee stings envenomation: a case report - Bhaskar, Atal; Singh, Gurpreet (International Journal of Research in Medical Sciences, 2022)
Bee stings are common in rural areas where people are engaged in farming and other allied occupations. They are classified under organic irritant poisons of animal origin. Usually, bee stings result in pain, itching and swelling. Rarely, they may cause death due to severe anaphylaxis. We report a case of death of a 65 year old male who was found dead near farmlands outside village. More than 100 bee stingers were present in situ on body at places. They were barbed and lodged into flesh. On internal examination, both lungs were found congested and edematous. Laryngeal apparatus was edematous with multiple petechiae present. Trachea was filled with whitish froth. The cause of death was opined as death due to anaphylactic shock consequent upon antemortem multiple bee stings envenomation.